2022
DOI: 10.1212/wnl.0000000000013316
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome After Endovascular Treatment in Patients With Active Cancer and Ischemic Stroke

Abstract: Objective:To explore clinical and safety outcomes of patients with acute ischemic stroke (AIS) and active cancer after endovascular treatment (EVT).Methods:Using data from the MR CLEAN Registry, we compared patients with active cancer (defined as cancer diagnosed within 12 months prior to stroke, metastatic disease, or current cancer treatment) to patients without cancer. Outcomes were 90-day modified Rankin Scale (mRS) score, mortality, successful reperfusion (eTICI scores≥2b), symptomatic intracranial hemorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 30 publications
(63 reference statements)
5
63
2
Order By: Relevance
“…We thank the authors for their contribution to an improved understanding of efficacy and complications of endovascular treatment (EVT) in patients with active malignancy. 1 The findings of the study that patients with active cancer experienced worse outcomes after EVT, even with favorable prestroke function and technical success, is in agreement with data from the ESCAPE and ESCAPE-NA1 trials of EVT. In both these trials, we found that experiencing comorbid cancer was strongly associated with poor functional outcomes according to the modified Rankin scale score in patients at 90 days, despite achieving small final infarct volumes after EVT.…”
supporting
confidence: 85%
“…We thank the authors for their contribution to an improved understanding of efficacy and complications of endovascular treatment (EVT) in patients with active malignancy. 1 The findings of the study that patients with active cancer experienced worse outcomes after EVT, even with favorable prestroke function and technical success, is in agreement with data from the ESCAPE and ESCAPE-NA1 trials of EVT. In both these trials, we found that experiencing comorbid cancer was strongly associated with poor functional outcomes according to the modified Rankin scale score in patients at 90 days, despite achieving small final infarct volumes after EVT.…”
supporting
confidence: 85%
“…We thank Moores and Ganesh for their comments on our research 1 and for drawing our attention to their 2 studies. 2,3 Both these studies report on 4 patients with cancer, but do not state whether the cancer was active.…”
mentioning
confidence: 99%
“…All of the included studies were retrospective analyses of either files/databases of patients that received acute treatment for AIS [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], or analyses of hospital records with the use of diagnostic codes, e.g., ICD codes for AIS and malignancy [ 20 , 21 , 22 ]. One study was a retrospective analysis of cancer patients from the MR CLEAN thrombectomy study registry [ 23 ].…”
Section: Resultsmentioning
confidence: 99%